Strategy for Increasing Competitiveness Based on Evaluation of Service Quality, Brand Image, Satisfaction, and Customer Loyalty in the Fresh Milk Beverage Shop Culinary Business - Risma Fitriani; Ade Momon Subagyo; Muhammad Rusli Arafat; Ghema Rivana (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2026)
The competition in the culinary industry has intensified, particularly among beverage shops offering fresh milk–based products. In this highly competitive environment, customers no longer evaluate products based solely on taste but also on the quality of service, the strength of the brand image, and the consistency of their overall experience. Field observations indicate ongoing issues, such as inconsistent service quality, a brand image that has not been strongly established, and varied levels of customer satisfaction all of which ultimately affect customer loyalty. These challenges highlight the need for data-driven strategies to strengthen business competitiveness. This study aims to analyze the influence of Service Quality, Brand Image, and Customer Satisfaction on Customer Loyalty, and to formulate the most appropriate strategy to enhance competitiveness in fresh milk beverage shops. A descriptive quantitative approach was applied by integrating the Analytical Hierarchy Process (AHP) to determine variable priorities and the Quantitative Strategic Planning Matrix (QSPM) to identify the most effective strategic alternatives. Data were collected through direct observation of service activities, interviews with the business owner, and questionnaires distributed to customers with prior purchase experience. Results indicate that service quality holds the highest weight in shaping customer loyalty, followed by brand image and customer satisfaction. Through QSPM analysis, the recommended priority strategies include strengthening service standards, enhancing brand identity through more effective communication, and developing customer loyalty programs to maintain long-term relationships. These findings provide a strategic foundation for fresh milk culinary businesses to adapt to competition and evolving customer preferences, ensuring sustainable growth and improved market positioning.